Identification of Urban Heat Island (UHI) in Bangkinang City Using Remote Sensing and Geographic Information System TechniquesUrban Heat Island (UHI Land Surface Temperature (LST) Citra Landsat - Tri Ananda, Shella; Adeswastoto, Hanantatur; setiawan, Beny (Journal of Engineering Science and Technology Management, 2024)
Bangkinang, the capital of Kampar District with an area of 177.2 km² and a population of 39,793, experiences a tropical climate that contributes to elevated surface temperatures. Increasing population, vehicle emissions, and industrial activities intensify urban heat, while limited vegetation density exacerbates the Urban Heat Island (UHI) effect. This study analyzes surface temperatures in 2021, 2022, and 2023 using Landsat 7 ETM+ and Landsat 8 OLI/TIRS data. Land Surface Temperature (LST) was calculated using the Single Channel Algorithm (SCA) method, resulting in average temperatures of 27.755°C (2021), 26.644°C (2022), and 27.130°C (2023). The Pearson correlation between LST and field temperature from BPS produced an Rxy value of 0.226, indicating a weak correlation. The UHI threshold analysis shows that the area affected by UHI decreased consistently from 2021 to 2023.